Influence of surface penetration on measured fluid force on a hand model - Kudo, S.; Vennell, R.; Wilson, B.; Waddell, N.; Sato, Y. (Journal of Biomechanics, 2008)
The purpose of this study was to quantify the effect of wave drag due to surface penetration on drag and lift forces (Cd and Cl) acting on a hand model. The values of Cd and Cl had been acquired to gain the hydrodynamic characteristics of the swimmer's hand and predict force on the swimmer's hand. These values have also been used to benchmark computational fluid dynamics analysis. Because the previous studies used a hand/forearm model which penetrated the water's surface, the values of Cd and Cl include the effect of the surface wave on the model. Wave formation causes pressure differences between the frontal and rear sides of a surface-penetrating model as a result of depressions and elevations in the water's surface. This may be considered as wave drag due to surface penetration. Fluid forces due to wave drag on the forearm should not be included in the measured Cd and Cl of a swimmer's hand that does not sweep near the water's surface. Two hand/forearm models are compared, one with the hand rigidly connected to the forearm. The other model was constructed to isolate the fluid forces acting on the hand from the influence of wave drag on the forearm. The measurements showed that the effect of wave drag on the hand model caused large increases in the values of Cd, up to 46-98% with lesser increases in Cl of 2-12% depending on the hand orientation. The present study provides an improved method to determine the values of Cd and Cl that eliminates the effect of wave drag on a hand/forearm model by isolating the measurement of fluid forces on the forearm of the hand/forearm model in order to separately acquire the forces on the hand.